Open educational resources (OER) in e-learning for higher education / Judith Gisip ... [et al.] - Gisip, Judith; Ibrahim, Norazura; Ratim, Suzana; Abdul Ghani, Fazni Susila (UiTM Press, 2024)
Open Educational Resources (OER) are educational materials that are freely accessible, openly licensed, and available for educators, learners, and the general public to use, share, and adapt. These resources can include a wide range of content, such as textbooks, lecture notes, videos, quizzes, simulations, lesson plans, and more. E-learning refers to the process of acquiring knowledge, skills, or information through digital technologies, typically delivered over the internet or through digital platforms. It involves the utilisation of various forms of electronic media and digital tools to facilitate learning and education. E-learning can take various forms such as online courses, virtual classrooms, webinars and interactive modules. The concepts can be configured as strategies to improve the quality of the curriculum in higher education institutions. The use of OER in e-learning is perceived by students as something interesting that can help them achieve a better understanding of various topics. This paper describes the characteristics of OER in e-learning, how OER are utilised within the context of e-learning, the benefits of using OER in e-learning, as well as the challenges to consider. Incorporating OER into e-learning has the potential to transform education, offering a promising approach to various platforms’ access to education, reducing costs, promoting collaboration, and fostering innovative teaching and learning experiences. As time progresses, the development of OER has proven beneficial and continues to drive growth within the education sector.